ELF exposure from mobile and cordless phones for the epidemiological MOBI-Kids study. (April 2017) - Calderón, Carolina; Ichikawa, Hiroki; Taki, Masao; Wake, Kanako; Addison, Darren; Mee, Terry; Maslanyj, Myron; Kromhout, Hans; Lee, Ae-Kyoung; Sim, Malcolm R; Wiart, Joe; Cardis, Elisabeth
Abstract: This paper describes measurements and computational modelling carried out in the MOBI-Kids case-control study to assess the extremely low frequency (ELF) exposure of the brain from use of mobile and cordless phones. Four different communication systems were investigated: Global System for Mobile (GSM), Universal Mobile Telecommunications System (UMTS), Digital Enhanced Cordless Telecommunications (DECT) and Wi-Fi Voice over Internet Protocol (VoIP). The magnetic fields produced by the phones during transmission were measured under controlled laboratory conditions, and an equivalent loop was fitted to the data to produce three-dimensional extrapolations of the field. Computational modelling was then used to calculate the induced current density and electric field strength in the brain resulting from exposure to these magnetic fields. Human voxel phantoms of four different ages were used: 8, 11, 14 and adult. The results indicate that the current densities induced in the brain during DECT calls are likely to be an order of magnitude lower than those generated during GSM calls but over twice that during UMTS calls. The average current density during Wi-Fi VoIP calls was found to be lower than for UMTS by 30%, but the variability across the samples investigated was high. Spectral contributions were important to consider in relation to current density, particularly for DECT phones. This study suggests that the spatial distribution of the ELF induced current densities in brain tissues is determined by the physical characteristics of the phone (in particular battery position) while the amplitude is mainly dependent on communication system, thus providing a feasible basis for assessing ELF exposure in the epidemiological study. The number of phantoms was not large enough to provide definitive evidence of an increase of induced current density with age, but the data that are available suggest that, if present, the effect is likely to be very small. Graphical abstract: Highlights: Mobile phones emit low frequency magnetic fields as well as radio frequencies. Epidemiological studies have not yet considered this exposure from handheld phones. The resulting induced current density (ICD) from GSM is10 fold larger than from DECT. Cordless phone induced current density is over double that from UMTS and VoIP (Wi-Fi). Age was not found to be an important determinant of the induced current density.